Relativistic compact anisotropic charged stellar models with Chaplygin equation of state - Bhar, Piyali; Murad, Mohammad Hassan (© Springer Science+Business Media Dordrecht 2016, 2016)
This article was published in the Astrophys Space Sci [© Springer Science+Business Media Dordrecht 2016] and the definite version is available at : http://10.1007/s10509-016-2923-9 The Journal's website is at: http://link.springer.com/article/10.1007/s10509-016-2923-9